Iran under the Pahlavi monarchy - Katouzian, Homa, author. aut Link Link Link
1 online resource.
Keywords: "Bringing together eighteen essays from Homa Katouzian, this book explores Iranian history, politics, culture, and Persian literature from mediaeval times through the nineteenth century and into the contemporary period. Beginning with an overview of mediaeval Iranian history, the book then considers developments in the nineteenth century, leading to the Constitutional Revolution of 1906-1911 which resulted in the fall of the Qajar dynasty (1785-1925). This is followed by a comprehensive overview of the Pahlavi Monarchy (1925-1979) and a new and original analysis of the Iranian revolution of February 1979. The book also includes essays on modern and classical Persian literature, encompassing Persian poetry and politics (1919-1925), the hitherto unstudied humour in Sadeq Hedayat's life and works, a critical study of Forugh Farrokhzad, a study of Persian literary devices with special reference to the great Persian classic Sa'di, and a study of Sa'di as a lover of beauty and advocate of human morality. The book analyses Iran in a way that has seldom been done in one single volume - the history of the Qajar and Pahlavi dynasties, the two great revolutions in the twentieth century, the unfamiliar nature of state and society in Iranian history, as well as some of the high points in modern and classical Persian literature - and is vital reading for anyone interested in the Middle East"-- Provided by publisher.